2022
DOI: 10.1155/2022/1393024
|View full text |Cite|
|
Sign up to set email alerts
|

Mining Geological Environment Monitoring and Real-Time Transmission Based on Internet of Things Technology

Abstract: A landslide monitoring technology based on BeiDouand, a wireless sensor network, is proposed in order to solve the problem that landslide has brought severe threat to people’s life and safety of property. The landslide monitoring system based on the BeiDouand wireless sensor network is analyzed and designed from the point of view of hardware and software. BeiDou message and GPRS double redundancy transmission mode are adopted to improve the reliability of transmission. It also adopts the factor compression met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%